The 5p15.33 locus is associated with risk of lung adenocarcinoma in never-smoking females in Asia. - Chao Agnes Hsiung; Qing Lan; Yun-Chul Hong; Chien-Jen Chen; H Dean Hosgood; I-Shou Chang; Nilanjan Chatterjee; Paul Brennan; Chen Wu; Wei Zheng; Gee-Chen Chang; Tangchun Wu; et al. (PLoS Genetics)
Genome-wide association studies of lung cancer reported in populations of European background have identified three regions on chromosomes 5p15.33, 6p21.33, and 15q25 that have achieved genome-wide significance with p-values of 10(-7) or lower. These studies have been performed primarily in cigarette smokers, raising the possibility that the observed associations could be related to tobacco use, lung carcinogenesis, or both. Since most women in Asia do not smoke, we conducted a genome-wide association study of lung adenocarcinoma in never-smoking females (584 cases, 585 controls) among Han Chinese in Taiwan and found that the most significant association was for rs2736100 on chromosome 5p15.33 (p = 1.30 x 10(-11)). This finding was independently replicated in seven studies from East Asia totaling 1,164 lung adenocarcinomas and 1,736 controls (p = 5.38 x 10(-11)). A pooled analysis achieved genome-wide significance for rs2736100. This SNP marker localizes to the CLPTM1L-TERT locus on chromosome 5p15.33 (p = 2.60 x 10(-20), allelic risk = 1.54, 95% Confidence Interval (CI) 1.41-1.68). Risks for heterozygote and homozygote carriers of the minor allele were 1.62 (95% CI; 1.40-1.87), and 2.35 (95% CI: 1.95-2.83), respectively. In summary, our results show that genetic variation in the CLPTM1L-TERT locus of chromosome 5p15.33 is directly associated with the risk of lung cancer, most notably adenocarcinoma.